Surm, lein ja mälestamine. Langenud sõdurite mälestamine külma sõja järgsel Saksamaal [Death, grief, and memory. Commemorating fallen soldiers in post Cold War Germany] - Echternkamp, Jörg (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2012)
The article explores the commemoration of fallen soldiers in West Germany since the end of World War II, focusing on the relation between the military and the society and drawing parallels to modern death cult.Longer version of the current abstract is included in the article, starting from p 199.